2018
DOI: 10.1590/1980-5373-mr-2018-0395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solid Solution + Double Ageing on Microstructure and Properties in the Layer by Layer of the Z-Y Interface of Inconel 718 alloys Fabricated by SLM

Abstract: The microstructure in the Z-Y surface of Inconel 718 alloys fabricated by selective laser melting (SLM) shows the relatively homogeneous and irregular fine grain structure after the heat treatment process of 1050ºC solid solution + double ageing. A large number of bulk precipitates were observed on the grain boundary, and the typical dendritic crystallization and Laves phases disappeared. It is possible that a large number of δ phases (NbNi 3) were precipitated on the grain boundary since the enrichment effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Figure 4(a) is for block 1, Figure 4(b) is for block 2, Figure 4(c) is for block 3, and Figure 4(d) is for block 4. SEM image of blocks reveals the presence of a dendritic solid solution of γ phases in addition to laves phases and precipitates of Nb, Mo, and Cr [26]. From the image, it can be observed that by increasing the percentage of IN625, the quantity of laves phase and precipitates are also increasing.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4(a) is for block 1, Figure 4(b) is for block 2, Figure 4(c) is for block 3, and Figure 4(d) is for block 4. SEM image of blocks reveals the presence of a dendritic solid solution of γ phases in addition to laves phases and precipitates of Nb, Mo, and Cr [26]. From the image, it can be observed that by increasing the percentage of IN625, the quantity of laves phase and precipitates are also increasing.…”
Section: Resultsmentioning
confidence: 99%
“…The heat treatment process will homogenize the segregation. As stated by Liu et al 20 ,when the heat treatment time is long enough, the δ phase will be generated. Based on this, the effect of different parameter on residual stress could be explained.…”
Section: Influences Of Processing Parameters On Residual Stressmentioning
confidence: 95%
“…From references [20][21][22] , it could be learned that a short heating and cooling time during SLM additive manufacturing may lead to a large number of segregation phases generation. The existing of segregation phase is the main factor generating residual stress, and the bigger ratio of segregation phase in the specimen results in a larger residual stress.…”
Section: Influences Of Processing Parameters On Residual Stressmentioning
confidence: 99%
“…They developed a control scheme for the laser plating process to achieve a low level of dilution and to reduce the width of the heat affected zone. Liu & all [35] studied the effect of combined heat treatment (solid solution 1050ºC + double aging) on IN718 laser-coated layers. They showed that the hardness increased from 350HV to 500HV and the residual stress turned into compression stress after the heat treatment.…”
Section: Introductionmentioning
confidence: 99%